2010
DOI: 10.1590/s1516-35982010001100009
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de forrageiras hibernais sob distintos níveis de luminosidade

Abstract: RESUMO -Objetivou-se determinar os possíveis efeitos da restrição de luminosidade, obtida com distintas densidades de árvores de Pinnus taeda, sobre a produção e qualidade de: aveia-preta (Avena strigosa Schreb) cv. Comum, aveia-branca (Avena sativa L.) cv. Fapa 2, azevém (Lolium multiflorum L.) cv. Comum, trigo (Triticum aestivum L.) duplo propósito cv.BRS Tarumã e ervilhaca peluda (Vicia villosa L.). Avaliaram-se três níveis de luminosidade: a sol aberto (sem presença de árvores de Pinnus taeda), 30% de rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
1
13
1
9
Order By: Relevance
“…Barro et al (2008) reported that a winter crop of black oats in Rio Grande do Sul, Brazil, grown with Pinus elliottii stands that intercepted 24% and 56% of incident light produced 25% (2907 kg/ha) and 58% (1627 kg/ha), respectively, of crops grown in full sun. Kirchner et al (2010) documented significant microclimatic changes in agroforestry systems with P. taeda in the wet subtropics, recording PAR interception in a stand spaced at 15 x 3 m as 30% in June and 66% in March-April. Under these conditions, the production of black oats was 1963 kg/ha, or 43% of that under full sun.…”
Section: Discussionmentioning
confidence: 99%
“…Barro et al (2008) reported that a winter crop of black oats in Rio Grande do Sul, Brazil, grown with Pinus elliottii stands that intercepted 24% and 56% of incident light produced 25% (2907 kg/ha) and 58% (1627 kg/ha), respectively, of crops grown in full sun. Kirchner et al (2010) documented significant microclimatic changes in agroforestry systems with P. taeda in the wet subtropics, recording PAR interception in a stand spaced at 15 x 3 m as 30% in June and 66% in March-April. Under these conditions, the production of black oats was 1963 kg/ha, or 43% of that under full sun.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, essa nova metodologia, respeitando a ecofi siologia das plantas, difi culta a comparação das espécies ou dos tratamentos numa mesma base de tempo, pois o corte/pastejo de um tratamento pode acontecer muito antes ou depois de outro tratamento. Provavelmente, devido a isso, os pesquisadores tenham preferido reportar e discutir dados apenas sobre a produção total de forragem (KIRCHNER et al, 2010;PIN et al, 2011). Baseado nesse contexto, objetivou-se com este trabalho, avaliar a dinâmica de produção de forrageiras anuais de inverno em quatro épocas de semeadura, por meio da avaliação da taxa de acúmulo diária de matéria seca, como indicador da dinâmica de produção de forragem.…”
Section: Introductionunclassified
“…La productividad de una pastura es un efecto directo de la cantidad de materia seca que una planta puede acumular, lo que depende de la cantidad de puntos de crecimiento que presenta cada planta (Kirchner, 2009). Similar a lo observado en este trabajo, Paciullo et al (2007), trabajando con Brachiaria decumbens, encontraron que bajo un nivel de 65% de sombreo la productividad total de la pastura se redujo en un 47%, como consecuencia de una reducción de la misma magnitud en la producción de macollos.…”
Section: Discussionunclassified
“…Tal como lo indica Kirchner (2009), la competencia por N se hace evidente entre los componentes del sistema. El N utilizado para la descomposición de las acículas, considerando su alta relación C:N, compite con las necesidades nutricionales de las plantas forrajeras, interfiriendo así en su producción de materia seca, sobre todo en el periodo invernal, en donde se produce la mayor acumulación de acículas sobre el estrato herbáceo.…”
Section: Discussionunclassified